2021
DOI: 10.1111/jnc.15257
|View full text |Cite
|
Sign up to set email alerts
|

α‐synuclein abnormalities trigger focal tau pathology, spreading to various brain areas in Parkinson disease

Abstract: Parkinson disease (PD) is the second most common neurodegenerative disorder, whose prevalence is 2~3% in the population over 65. α-Synuclein aggregation is the major pathological hallmark of PD. However, recent studies have demonstrated enhancing evidence of tau pathology in PD. Despite extensive considerations, thus far, the actual spreading mechanism of neurodegeneration has remained elusive in a PD brain. This study aimed to further investigate the development of α-synuclein and tau pathology. We employed v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 153 publications
(209 reference statements)
0
12
0
Order By: Relevance
“…In a postmortem study, co‐aggregation of tau protein and α‐syn was observed in LBs (Ishizawa et al, 2003). In various PD models, α‐syn has been shown to trigger focal tau pathology and promote the phosphorylation of tau; in addition, increased p‐tau concentrations have been found in the striatum of PD patients (Duka et al, 2009; Hadi et al, 2021; Haggerty et al, 2011). Moreover, longitudinal follow‐up studies have proven that high p‐tau levels in CSF are associated with worsening motor symptoms (Hall et al, 2015; Hall et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a postmortem study, co‐aggregation of tau protein and α‐syn was observed in LBs (Ishizawa et al, 2003). In various PD models, α‐syn has been shown to trigger focal tau pathology and promote the phosphorylation of tau; in addition, increased p‐tau concentrations have been found in the striatum of PD patients (Duka et al, 2009; Hadi et al, 2021; Haggerty et al, 2011). Moreover, longitudinal follow‐up studies have proven that high p‐tau levels in CSF are associated with worsening motor symptoms (Hall et al, 2015; Hall et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while our MMD cases indicate that tau, and not α-syn, are critical for early manifestation of the disease, we cannot currently rule out and interaction in later disease. This morphological feature demonstrated that tau and α-syn may interact and the interaction may play an important role on the development and spreading of neurodegeneration[20, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular models have verified that pre-formed α-syn fibrils cross-seed intracellular tau to induce neurofibrillary tangle formation[23]. α-syn phosphorylation triggers tau pathogenicity and induces widespread phosphorylated tau with prion-like nature in various brain areas[28]. High levels of S396 phospho-tau and phospho-α-syn were found in synaptic-enriched fractions of the frontal cortex in Alzheimer’s disease and PD[42].…”
Section: Discussionmentioning
confidence: 99%
“…For isolation of primary cortical neurons from the brain of mice embryos, to reduce brain cell death and brain injury, pregnant mice were euthanized by decapitation as previously described (Seibenhener & Wooten, 2012). After isolation of 17-day-old embryos (E17) from the uterus of pregnant mice, primary cortical neurons were isolated from the embryonic (E17) mouse cerebral cortex as described in the previous publication (Hadi, Akrami, Totonchi, et al, 2020). Isolated cortical tissues were digested with a digestion solution that contained trypsin-EDTA (0.25%) (Gibco, 25200056), DNase I (1 μg/ml) (Roche, 11284932001), HEPES (1M, pH: 7-7.6) (Sigma-Aldrich, H0887) and D-glucose (DG) (1M) (Sigma-Aldrich, D8270).…”
Section: Primary Cortical Neuron Culturementioning
confidence: 99%
“…Pin1 suppression induces cis P‐tau accumulation (Chen et al, 2015; Nakamura et al, 2012). It has been proposed that cis P‐tau is highly neurotoxic and is an early driver of the tau pathology process upon traumatic brain injury (TBI), chronic traumatic encephalopathy, Alzheimer's disease, Parkinson disease and bipolar disorder (Albayram et al, 2017; Hadi, Akrami, Totonchi, et al, 2020; Kondo et al, 2015; Nakamura et al, 2012; Naserkhaki et al, 2019). It has been demonstrated that various stresses, such as hypoxia or nutritional starvation, suppress Pin1 in various manners, whereby induce cis P‐tau in cultured neurons (Kondo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%